Current practices of urologists regarding intravesical therapy use for non-muscle-invasive bladder cancer patients. - Muhammad Farhan; Ahmed , Syed Farhan; Mithani, Hammad; Aziz, Wajahat; Syed Muhammad Nazim; Zia, Muhammad Khurram (International Journal of Endorsing Health Science Research, 2022)
Background: Leading urology guidelines recommend intravesical chemotherapy and immunotherapy for non-muscle invasive bladder cancer (NMIBC) to reduce the risk of recurrence and progression. This study aims to evaluate the self-reported practices regarding intravesical therapy use for patients with non-muscle-invasive bladder cancer among urologists in Karachi. Methodology: In this cross-sectional study, a proforma-based survey was conducted between January and March 2018, in which printed questionnaires regarding adjuvant treatment options for NMIBC were administered and collected by primary investigators among urologists in leading institutions of Karachi. Results: Overall, 80% of respondents reported routine administration of single instillation of intravesical chemotherapy (SICA) after transurethral resection of bladder tumor (TURBT), and almost one-third of them (37.3%) give SICA within 6 hours inward. A quarter of respondents practice induction therapy routinely in low-risk BC using Mitomycin, whereas 76.5% in high-risk cases use Bacillus Calmette Geurin (BCG) as immunotherapy. Regarding the time duration of intravesical therapy installation, most of the urologists reported for 45 mins (49%) followed by 30 mins (29.4%), 2 hrs (17.6%), and 3 hrs (3.9%). Only 39% reported routinely using maintenance therapy with BCG for high-risk BC. As for BCG failure, 76.5% of participants reported radical cystectomy. Conclusion: Our survey results provide evidence of variation in practices among urologists and poor guideline adherence with the risk of under-treatment of patients with NMIBC. This requires joint efforts of all those involved in the treatment of non-muscle invasive bladder cancer to improve the quality of care.